Peiper w Madrycie, czyli hiszpański topos - Kluba, BAgnieszka (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
The pope of Polish avant-garde is a main character of a certain persistently recollected critical topos. It claims that, after spending World War I in Europe, Tadeusz Peiper took a basic shape of his poetical idea from avant-garde artists he then met. Critics who share this opinion believe that Peiper, aware of these “borrowings”, was developing a carefully planned strategy in order to conceal those external sources and to pretend originality. The author of the article disavows these harmful assumptions, reconstructing their possible genesis (rooted in and continued prewar suspicions of plagiarism) and analyzing some of their critical versions. In the same time she presents wider and not only avant-garde background of Peiper’s idea (baroque, gongorism).
Peiper in Madrid or the Spanish topos